The Nature of Law and Potential Coercion - Woodbury-Smith, Kara (My University, 2020)
This thesis argues for a novel understanding of the relationship between law and coercion. One of the relationships H.L.A. Hart sought to clarify is between law and coercion. In his work, Hart denies that coercion is a conceptually necessary feature of law – denies that the existence of law is in some sense determined by the presence of coercive mechanisms. According to Hart, coercion is naturally necessary to our legal practices. We humans need our law to be backed by coercive mechanisms so that it can do what it is supposed to: serve as an authoritative guide for behaviour. Investigating the relationship between law and coercion not only depends on what one thinks about law, but also what one means by ‘coercion.’ I define an instance of coercion as a forced-choice. I also explain that understanding what it means to say, ‘law coerces’ is made difficult by the fact that what is coercive for one person may not be coercive for another. This subjective aspect of coercion means that more specific questions need to be asked in order to understand the relationship between law and coercion. This thesis asks: is there a conceptual relationship between law and the law’s institutionalisation and utilisation of coercive mechanisms? I argue that coercive mechanisms are not a conceptually necessary feature of law. I also argue that Hart’s work still leaves the relationship between law and coercion problematically undefined. Rather, I put forward the claim that law is coercion-apt. I expand this claim by distinguishing law from other normative systems, like morality. Unlike law, morality, I argue, is not coercion-apt. Therefore, this thesis not only refines our understanding of the relationship between law and coercion, but also between law and morality – which is another relationship Hart sought to clarify in his work.
Keywords: Legal philosophy; Law; Coercion; Morality